The palaeomagnetism of the central zone of the Lewisian foreland, north-west Scotland - Piper, J. D. A. (Geophysical Journal International, 1979)
Three principal directions of magnetization are recognized in the central part of the Lewisian metamorphic terrain of north-west Scotland. The first (‘A’) magnetization is a high blocking temperature component residing in magnetite and imposed during post-Laxfordian uplift and cooling. Fifty sites yield an overall mean D = 285.9°, I = 54.9° and palaeomagnetic pole at 273.2° E, 37.6° N ( dp = 3.7°, dm = 5.2°); this magnetization was probably acquired at crustal depths of 6–10 km and is linked to K—Ar uplift ages averaging 1650–1625 Ma. The second (‘B’) magnetizations are defined by E—W directions and also reside in high blocking temperature components; they are, however, dipolar, have some properties distinct from the ‘A’ magnetizations, and are correlated with late stages in the history of the complex at 1400–1200 Ma. The third (‘C’) NE directed magnetizations reside predominantly in low blocking temperature components in pyrrhotite and possibly maghemite, and were probably acquired at a late stage of the regional uplift; they do not correlate with post-1450 Ma magnetizations from the Laurentian Shield and probably relate to the as yet undefined interval 1600–1450 Ma. The collective palaeomagnetic data and certain geologic data suggest that the Lewisian foreland should be rotated by 30° clockwise about a local axis of rotation on the conventional reconstruction of the North Atlantic continents; this rotation is associated with Lower Palaeozoic trans-current movements and may be related to a fourth (‘D’) magnetization of viscous origin. A collective assessment of 1850–1600 Ma palaeomagnetic data for the Laurentian Shield defines a large apw loop; there is widespread agreement between data from the constituent structural provinces of the Shield although different metamorphic regions define complementary segments of the loop related to uplift over different intervals of time.